Moral identity on athletes’ prosocial and antisocial behavior perceived by gender - Mohammad Fazilah, Fariha; Mohd Kassim, Ahmad Fikri; Mohd Ezam Edros, Nor Nandinie (GADING Journal for the Social Sciences, 2024)
Moral identity is a self-regulatory mechanism in which the conception of morality can vary from one individual to another. For example, one person may emphasize fairness as central to their morality, even as another accentuates kindness. It is prominent in the social cognitive view, which explains moral identity as increasing the accessibility of self-regulatory schemas that regulate moral behaviour. Moral identity is “a self-conception structured around a set of moral traits”. The centrality of morality to an individual‟s identity builds chronically accessible self-schemas and moral behaviours such as prosocial and antisocial athletes‟ behaviour. Thus, the purpose of this study is to evaluate the value of moral identity in athletes‟ behaviour. This is observable in the environment of developing athlete‟s dependent on gender. A questionnaire based on Moral Identity was completed by 240 university athletes from the northern region universities in Malaysia. The finding showed that there was no significant difference in the positive moral identity subscale among gender. Females are becoming socialised into sports by a process like males and learning values, norms, and character like males. Meanwhile, there was a significant difference in negative moral identity among gender. Female athletes adopt athletic moral and ethical behaviours much more in comparison with male athletes. Looking at the nature of male athletes themselves, their moral character is stricter and less spoiled than that of females. Works on promoting individuals‟ moral identity should be encouraged to facilitate the effect of moral emotions on moral actions.